Pengabdian Kepada Masyarakat Melalui Rapat Koordinasi Majelis Ulama Indonesia (MUI) Kabupaten Kutai Timur - Yasin, Muhammad; Faelasup, Faelasup; Basir, M. Abdul; Gozali, Imron (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
The Indonesian Ulema Council (MUI) itself has duties and responsibilities Providing oversight for Muslims Providing education and guidance for adherents of Islam, Recruiting better cadres, Providing a way out of problems related to religion in the international world, Forming the concept of Islamic education, Overseeing content in the mass media and Running cooperation with various religious organisations Increasing faith, morals, and Sharia where the coordination meeting of the MUI of East Kutai Regency aims to increase belief, character, and Islamic law in Indonesian society Cooperation Development where the coordination meeting of the MUI of East Kutai Regency becomes a forum for safety and cooperation between various parties, including ulama, government, Islamic scholars and companies The influence of leadership in the Coordination Meeting of MUI of Kutai Timur Regency shows the importance of the leader's role in leading and controlling Muslims, as well as maintaining the interests of the ummah in Indonesia and The evaluation of this activity is very important because the Coordination Meeting of MUI shows the importance of evaluation in evaluating the extent to which the activity has achieved the goals that have been set, as well as to find the weak points of the implementation of the activity and provide recommendations for improvement so that the activity can run more effectively in the future.